As pesquisas produzidas pelos docentes do Instituto Federal de São Paulo/Campus Suzano e suas relações com ensino e extensão (2013 – 2020) - Ferreira, Maria Aparecida Bueno (2023)
This work has the objective to investigate the research carried out by professors at the Federal Institute of Education, Science and Technology of São Paulo/Campus Suzano and their relationship with teaching and extension activities. It starts from the assumption that the inseparability between teaching, research and extension is advocated by the legislation that governs technological higher education in the country, however, the reference bibliography and the results obtained indicate that the effective implementation of this legal provision is quite complex and finds obstacles that vary according to the reality of each institution. Using the theoretical-methodological framework of Oral History, through thematic interviews, some surveys carried out between 2013 and 2020 by teachers at Campus Suzano were mapped. Those involved with academic production were also identified (teachers, students, companies and non governmental organizations) and how thes researches were articulated with teaching and extension activities was discussed. Gatti (2002), Gadotti (2017), Moita and Andrade (2009) and Nogueira (2005) were taken as references in the definition of the teaching, research and extension tripod, as well as the legislation corresponding to the theme. It was verified the lack of systematization of the researches and the existence of a departmental structure that does not favor the articulation between research and extension, since there is an Extension Coordination and another one of Research and Innovation, constituting isolated systems. Barriers related to the legislation that governs the hiring of professors and the lack of active participation of administrative technicians in the projects were also found. In addition, the testimonies also show that the challenges that are part of the Institutional Development Plan are, in some way, present in the research and/or extension projects they carry out. With regard to the institution, the interviewees point out the need to expand research laboratories, provide funds for their development and hold meetings to disseminate the productions carried out